2016
DOI: 10.1111/add.13329
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of neuropsychiatric adverse events during early treatment with varenicline or a nicotine patch

Abstract: In US VA patients studied prior to the boxed warning being implemented, use of varenicline for smoking cessation was not associated with a detectable increase compared with nicotine patches in hospitalization for any mental health outcomes. There was an increased rate of out-patient attendances with a primary diagnosis of schizophrenia amounting to five per 100 person years of treatment. This increase was found only in patients with a pre-existing mental health disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…With regard to neuropsychiatric events, a recent trial in 8144 smokers with and without psychiatric disorders found no significant increase in neuropsychiatric adverse events attributable to varenicline relative to nicotine patch or placebo 6. Previous observational studies also found no association between varenicline use and neuropsychiatric risks 11 21 22 28 29…”
Section: Discussionmentioning
confidence: 99%
“…With regard to neuropsychiatric events, a recent trial in 8144 smokers with and without psychiatric disorders found no significant increase in neuropsychiatric adverse events attributable to varenicline relative to nicotine patch or placebo 6. Previous observational studies also found no association between varenicline use and neuropsychiatric risks 11 21 22 28 29…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the model does not include possible costs or effects of adverse events of varenicline. However, recent studies have not shown an adverse safety profile for varenicline 57, 58, 59, 60, 61, 62. Close collaboration with stakeholders and experts in the field of smoking cessation both nationally and internationally allowed us to evaluate interventions for which no effectiveness data could be identified for Germany.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies. Several large retrospective observational cohort studies, looking at a variety of endpoint measures, have investigated whether varenicline is associated with an increased risk of neuropsychiatric AEs, using NRT or bupropion as a comparator 88,[96][97][98][99][100][101][102] (Supplementary Table 3). Four of these studies [98][99][100][101] are included in varenicline prescribing information.…”
Section: Current Medical Research and Opinionmentioning
confidence: 99%
“…One study analyzed data in the QResearch database to look at the incidence of fatal and non-fatal selfharm and depression within 6 months of treatment with varenicline or NRT and found no increased risk for these events versus NRT 88 . Another study compared inpatient discharge diagnosis for seven separate psychiatric conditions within 30 days of treatment initiation in smokers using varenicline (N ¼ 11,774) versus NRT (N ¼ 23,548) and reported no between-treatment differences 96 . A secondary endpoint looking at outpatient visits for these same disorders found no differences except for schizophrenia.…”
Section: Current Medical Research and Opinionmentioning
confidence: 99%